Blink synkinesis monitoring during microvascular decompression for hemifacial spasm. Issue 6 (June 2019) - Hsu, Po-Cheng; Yang, Tsui-Fen; Hsu, Sanford P.C.; Yen, Yu-Shu; Lin, Chun-Fu; Tsai, Yuan-Yuan; Chou, Chen-Liang; Wu, Han-Lin
Abstract : Background: In the present study, we investigated whether blink synkinesis monitoring during microvascular decompression (MVD) is effective for predicting long-term outcomes in patients with hemifacial spasm (HFS). Methods: This retrospective study included 69 patients who had undergone MVD for HFS at a tertiary hospital. All patients underwent intraoperative monitoring of blink synkinesis, lateral spread responses (LSRs), and facial nerve motor-evoked potentials (FNMEPs). Baseline signals were compared to those obtained following decompression with Teflon, and postoperative outcomes were recorded. Results: A total of 65 patients were observed with complete relief of symptoms after 1 year after MVD, while 61 patients were observed with initial disappearance of blink synkinesis, 57 patients were observed with initial elimination of the LSR, and 45 patients with initial decreases in FNMEP amplitude (>50%). The highest sensitivity and accuracy values were observed for blink synkinesis. Chi-square tests comparing the sensitivity of the three methods revealed that FNMEP monitoring was associated with significantly lower sensitivity values than the remaining methods. Combined use of blink synkinesis and LSRs did not significantly increase sensitivity (61/65 vs 62/65) or accuracy (62/69 vs 63/69). Conclusion: Our results demonstrate that blink synkinesis monitoring is safe during MVD for HFS. Furthermore, blink synkinesis was associated with the highest sensitivity and predictive values among the three methods evaluated. These findings suggest that blink synkinesis can be regarded as the first choice for intraoperative monitoring during MVD. Concurrent use of blink synkinesis and LSR monitoring may maximize the ability to predict patient prognosis and determine the extent of decompression.